How to Live : 1. How We Are - Deary, Vincent (London Allen Lane, 2014)
We live in small worlds. An astonishing literary debut and the first book in the monumental How To Live trilogy, How We Are explores the power of habit and the difficulty of change. A story told in three parts, this profound and ambitious trilogy gets right to the heart of what it means to be human: how we work, how we break, and how we mend. As Vincent Deary shows us, we live most of our lives automatically, in small worlds of more or less comfortable routine - what he calls Act One. Conscious change requires deliberate effort, and so, for the most part, we avoid it. But inevitably, from within or without, something will come along to disturb our small worlds - some News From Elsewhere. And with ingrained reluctance, we begin the work of adjustment: Act Two. Over decades of psychotherapeutic work, Deary has been a witness to the theatre of change - the way that ordinary people get stuck, struggle with new circumstances, and eventually transform their lives and get better. He is also keenly aware that novelists, poets, philosophers and theologians have grappled with these experiences for far longer than psychologists have. Drawing on his own personal experience, and a staggering range of literary, philosophical and cultural sources, Deary has produced a mesmerizing and universal portrait of the human condition. Part psychologist, part philosopher, part novelist, Deary helps us to see how we can resist being mere habit machines, and make our acts and our lives more fully our own. Vincent Deary is a health psychologist at Northumbria University. This, his first book, is part one of the How To Live trilogy, and will be followed by How We Break (book 2) and How We Mend (book 3).
Keywords: Human beings -- Psychology--Philosophy -- Change